What shapes older adults’ multidimensional well-being in Jambi Province, Indonesia? Integrating capability–ecological frameworks - Hardiani, Hardiani; Junaidi, Junaidi; Suri, Putri Intan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
This study examines the socioeconomic determinants of subjective well-being (SWB) among older adults in Jambi Province, Indonesia, using a multidimensional framework encompassing life satisfaction, emotional well-being, and life meaning. Addressing limitations in prior research that often employ unidimensional measures or neglect contextual factors, this study integrates individual and environmental perspectives. A cross-sectional survey of 207 individuals aged 60 and above was conducted between July and August 2024 using stratified random sampling. Multiple linear regression was employed for analysis. The findings reveal that gender, educational attainment, and household role consistently and positively influence all dimensions of SWB. Economic activity status, income, ethnicity, and residential area also contribute to variation, although their effects are mixed. Chronological age showed no significant association with SWB. Interpreted through the Capability Approach and the Ecological Model of Aging, the results highlight how individual capacities and contextual conditions jointly shape well-being in later life. The study highlights the importance of implementing integrated policy measures, including inclusive pension systems, lifelong learning programs, and age-friendly infrastructure, to improve economic security and social inclusion for older adults.